2014
DOI: 10.1108/cw-09-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

Method development for the cyclic characterization of thin copper layers for PCB applications

Abstract: Purpose -The overall aim of this research work was the improvement of the failure behavior of printed circuit boards (PCBs). In order to describe the mechanical behavior of PCBs under cyclic thermal loads, thin copper layers were characterized. The mechanical properties of these copper layers were determined in cyclic four-point bend tests and in cyclic tensile-compression tests, as their behavior under changing tensile and compression loads needed to be evaluated. Design/methodology/approach -Specimens for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Specimens consisting of alternating layers of copper and FR4-prepreg were used; a suitable fixture was developed in earlier work. 24 It was installed in a MTS 810-22 (MTS, Eden Prairie, MN, USA) testing machine for the measurements at 23 °C and in a MTS 831 testing machine for the measurements at 85 °C and 145 °C. The gage length was 5 mm to avoid buckling.…”
Section: Experimental Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Specimens consisting of alternating layers of copper and FR4-prepreg were used; a suitable fixture was developed in earlier work. 24 It was installed in a MTS 810-22 (MTS, Eden Prairie, MN, USA) testing machine for the measurements at 23 °C and in a MTS 831 testing machine for the measurements at 85 °C and 145 °C. The gage length was 5 mm to avoid buckling.…”
Section: Experimental Characterizationmentioning
confidence: 99%
“…They were calculated by micromechanic simulations. The measurements and the complementary simulations are described in detail in Fellner et al, 24 Fuchs et al 30 and Fellner. 31 The elastic properties of the copper foil were measured using a micro-dynamic mechanical analyzer.…”
Section: Experimental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus from the overall and substrate responses, the authors were able to define the stress-strain response of the copper alone, nevertheless neglecting the transversal stress induced in the film due to the mismatch in Poisson's ratio between the substrate and the copper film. One can also refer to Mönig et al (2004), Kraft et al (2001) or Fellner et al (2014) for similar experiments and copper characterization. It has been also observed that microstructural features influence the mechanical response of copper film.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the low processing temperature makes Cu as an ideal internal electrodes for MLCs . It is well‐known that Cu electrodes have been widely used in the PCBs and IC chips . The low processing temperature avoids the oxidation of Cu layers during the thermal processing of the MLCs.…”
Section: Introductionmentioning
confidence: 99%